Hospitals in Iran and India, 1500-1950s - Speziale, Fabrizio, 1968- (Iran Studies, 2012)
This volume looks at hospitals in the post-medieval Indo-Iranian world from various perspectives. During the Safavid-Mughal periods hospitals were still tied to Avicennian medicine. However, in Qajar Iran and British India hospitals became important instruments for the spread of modern Western medicine. The papers in this volume present a significant panorama on the history of medicine and medical institutions in Iran and India during the early modern and the modern periods. The portrait that emerges is not homogeneous, but instead shows ambivalent and contrasting images. Hospitals can be seen as powerful symbols of the Muslim scientific civilization and then of modern medicine, nevertheless, they remained institutions relegated to the fringes of society - regarded with suspicion and usually reserved for the poor. Contributors include: Cristiana Bastos, Willem Floor, Claudia Preckel, Omid Rezai, Fabrizio Speziale, Hasan Tadjbakhsh, Anna Vanzan This book is copublished with the Institut Français de Recherche en Iran (IFRI) as numbers 74 in the Bibliothéque Iranienne series. Le présent ouvrage propose un panorama significatif d'études portant sur l'histoire et le rôle des hôpitaux dans le monde irano-indien au cours de la première modernité et de l'époque moderne. Les contributions rassemblées dans ce volume étudient l'hôpital depuis plusieurs perspectives, examinant cet établissement tantôt comme une institution scientifique, tantôt en fonction de son utilité sociale. Ce qui émerge de ces travaux ne constitue pas un portrait homogène, mais plutôt une image ambivalente et contrastée de ces établissements. Les hôpitaux peuvent être vus comme des symboles puissants de la piété des souverains musulmans, ou de la civilisation scientifique musulmane, puis du triomphe de la science occidentale moderne. Cependant, pour une très longue période, l'hôpital demeure une institution reléguée à la marge de la société, regardée avec suspicion et en particulier réservée aux indigents. Ce livre est une coédition avec l'Institut Français de Recherche en Iran (IFRI) comme n◦ 74 dans la série Bibliothèque Iranienne